Kualitas Benih dan Pertumbuhan Bibit Tanaman Iles-Iles (Amorphophallus muelleri Blume) Asal Media Tumbuh Berbeda - Maryati Sari; Edi Santosa; Adolf Pieter Lontoh; Ani Kurniawati (Jurnal Ilmu Pertanian Indonesia, 2019)
Most of Amorphophallus muelleri seeds for corm production derives from natural production in the forest. The objective of research was to evaluate seed quality and seedling growth from natural and gibberellin (GA3)-induced flowering, and different growing media in order to develop seed production technology. The experiments were conducted at Leuwikopo Experimental Farm of Bogor Agricultural University, Bogor, Indonesia from August 2016-April 2017. A. muelleri seeds from six culture practices were compared, i.e., mother corms with natural flowering were planted in soil media, soil+rice husk charcoal, and soil+cow manure, and mother corms induced flowering using GA3 (1.000, 1.500, and 2000 ppm) were planted in soil media. Results indicated that berry size, color, seed color and size and seed germination rate were independent of seed production method, i.e., non-induction, GA3 induction, and growing media. Germination rate was >90%, and no abnormal sprouting was found. The highest seedling establishment, represented by full-expand of first leaf, was obtained from seeds of soil+rice husk charcoal media. Seedling from seeds of soil+rice husk charcoal and soil+cow manure media had larger leaves than the other treatments. Present study implies that application of rice husk charcoal or manure in the seed production of A. muelleri is important to obtain high quality seedling.